Selective posterior callosotomy for drop attacks: A new approach sparing prefrontal connectivity. (8th November 2016) - Paglioli, Eliseu; Martins, William Alves; Azambuja, Ney; Portuguez, Mirna; Frigeri, Thomas More; Pinos, Larissa; Saute, Ricardo; Salles, Cora; Hoefel, João Rubião; Soder, Ricardo Bernardi; da Costa, Jaderson Costa; Hemb, Marta; et al.
Abstract : Objective: To evaluate a novel approach to control epileptic drop attacks through a selective posterior callosotomy, sparing all prefrontal interconnectivity. Methods: Thirty-six patients with refractory drop attacks had selective posterior callosotomy and prospective follow-up for >4 years. Falls, episodes of aggressive behavior, and IQ were quantified. Autonomy in activities of daily living, axial tonus, and speech generated a functional score ranging from 0 to 13. Subjective effect on patient well-being and caregiver burden was also assessed. Results: Median monthly frequency of drop attacks decreased from 150 to 0.5. Thirty patients (83%) achieved either complete or >90% control of the falls. Need for constant supervision decreased from 90% to 36% of patients. All had estimated IQ below 85. Median functional score increased from 7 to 10 ( p = 0.03). No patient had decrease in speech fluency or hemiparesis. Caregivers rated the effect of the procedure as excellent in 40% and as having greatly improved functioning in another 50%. Clinical, EEG, imaging, and cognitive variables did not correlate with outcome. Conclusions: This cohort study with objective outcome assessment suggests that selective posterior callosotomy is safe and effective to control drop attacks, with functional and behavioral gains in patients with intellectual disability. Results are comparable to historical series of total callosotomy and suggest that anterior callosal fibers may be spared. Classification of evidence: This study provides Class III evidence that selective posterior callosotomy reduces falls in patients with epileptic drop attacks.